Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1074/jbc.m606412200
|View full text |Cite
|
Sign up to set email alerts
|

Perlecan Proteolysis Induces an α2β1 Integrin- and Src Family Kinase-dependent Anti-apoptotic Pathway in Fibroblasts in the Absence of Focal Adhesion Kinase Activation

Abstract: Dysregulation of apoptosis in endothelial cells (EC) and fibroblasts contributes to fibrosis. We have shown previously that apoptosis of EC triggers the proteolysis of extracellular matrix components and the release of a C-terminal fragment of perlecan, which in turn inhibits apoptosis of fibroblasts. Here we have defined the receptors and pathways implicated in this anti-apoptotic response in fibroblasts. Neutralizing ␣2␤1 integrin activity in fibroblasts exposed to either medium conditioned by apoptotic EC (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 41 publications
6
89
1
Order By: Relevance
“…Co-incubation with PP2 and LY2940002, inhibitors of SFK and PI3K, respectively, blocked CTGFdependent aSMA upregulation in human and mouse fibroblasts ( Figure 7b and Supplementary Figure 5). In agreement with our previous work, 15,16 heightened Akt phosphorylation was found in fibroblasts exposed to SSC (Figure 7c). CTGF also increased Akt phosphorylation in fibroblasts, which was inhibited in the presence of PP2 (Figure 7c).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Co-incubation with PP2 and LY2940002, inhibitors of SFK and PI3K, respectively, blocked CTGFdependent aSMA upregulation in human and mouse fibroblasts ( Figure 7b and Supplementary Figure 5). In agreement with our previous work, 15,16 heightened Akt phosphorylation was found in fibroblasts exposed to SSC (Figure 7c). CTGF also increased Akt phosphorylation in fibroblasts, which was inhibited in the presence of PP2 (Figure 7c).…”
Section: Resultssupporting
confidence: 93%
“…We showed previously that caspase-3 activation in ECs triggers the release of the C-terminal laminin G motif of perlecan (LG3). 8,16 Yet, fibroblasts exposed to LG3 in vitro failed to differentiate into myofibroblasts (Supplementary Figure 3). This suggested that caspase-3 activation supports the release of various mediators active on target cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BMP1/TLD-like proteinase cleavage site for LG3 is identical to the site at which perlecan is cleaved in vivo to produce LG3 fragments found in the urine of patients with end-stage renal disease (Oda et al, 1996) and in the amniotic fluid of pregnant women with ruptured fetal membranes (Vuadens et al, 2003), suggesting that cleavage by these proteinases is physiologically relevant. Recently, the LG3 domain was also shown to promote apoptosis-resistance in fibroblasts via interactions with α2β1 integrins (Laplante et al, 2006). As accumulation of apoptosis resistant fibroblasts may be a hallmark of fibrosis (Arora and McCulloch, 1999;Desmouliere et al, 1995), proteolytic processing of perlecan by BMP1/TLD-like proteinases may have functional implications in both angiogenesis and fibrosis.…”
Section: Non-collagenous Matrix Proteinsmentioning
confidence: 99%